The Impact of the COVID-19 Pandemic on Surgical Practices in Ophthalmology at the National Referral Hospital in Yogyakarta: Doi: 10.36351/pjo.v41i2.1987 - Pradhanika, Nalam Taqi Kayana; Mahayana, Indra Tri; Setyowati, Reny; Wardhana, Firman Setya (Pakistan Journal of Ophthalmology, 2025)
Purpose: To assess the impact of the COVID-19 pandemic on ophthalmic surgical practices at the National Referral Hospital in Yogyakarta by comparing surgical data from the pre-pandemic period with data collected during the pandemic. Study Design: Retrospective comparative study. Methods: Patient data were divided into two groups: pre-COVID and during-COVID. Demographic and surgical data were collected. Continuous variables (e.g., patient age, number of surgeries) were presented as mean ± standard deviation (SD), while categorical variables (e.g., type of surgery, gender distribution) were presented as frequencies and percentages. A paired t-test was used to compare continuous variables, and the Chi-square test was applied to compare proportions (e.g., elective vs. emergency surgeries). Statistical analysis was conducted using SPSS 25.0, with p < 0.05 considered statistically significant. Results: Among 4,578 patients, there was a +11.73% increase in total surgeries from pre-COVID to the COVID era (p > 0.05). Based on surgery type, elective surgeries increased by +15.56% (p > 0.05), while emergency surgeries significantly decreased by -60.51% (p < 0.05).Cataract & Refractive Surgery, Glaucoma, Vitreo-Retinal Surgery, Infection & Immunology Surgery increased by +4.83% (p > 0.05), +103.5% (p < 0.05), +5.63% (p > 0.05), +7.28% (p < 0.05) and +26.8% (p > 0.05) respectively. While reconstructive, oculoplastic &oncology Surgery decreased by -5.36% (p > 0.05). Conclusion: The COVID-19 pandemic led to a significant decrease in emergency surgeries while increasing elective procedures, particularly in glaucoma and pediatric ophthalmology.